Tutorías de acompañamiento en el proceso de formación académica con los estudiantes de la Facultad de Ciencias de la Educación de la Universidad Estatal de Bolívar, periodo octubre 2023-febrero 2024 - Peña Mazabanda, Fernanda Masherly (2024)
The purpose of this research is to promote student accompaniment tutorials in the academic training process with students of the Faculty of Education Sciences of the State University of Bolívar, period October 2023 and February 2024. In the first instance, responding to the first and second objectives through the theoretical foundations and the application of relevant research methods, the effectiveness of the Tutorials as support in academic training is determined, considering aspects such as: the relationship with the educational environment, academic performance, educational resources, support in a subject, physical, psychological, family, social, emotional health and special needs. Qualitative data are collected to evaluate the aspects that students consider to improve academic performance or not to abandon their studies, on the usefulness and effectiveness of tutoring. This research addresses the problem of academic repetition and dropout in the student training process. Responding to the third objective of this research, it has been to propose a didactic guide applying the ADDIE model on Student Accompaniment Tutoring, focused on the university context and adapted to the guidelines of the State University of Bolívar, which was approved by the University Council in the year 2014, where the tutor teacher plays the key role in carrying out this type of tutoring, contributing to the comprehensive development of the student. The results obtained provide valuable perspectives on the effectiveness of the accompaniment tutoring program, promoting improving and strengthening the tutoring process, with a more effective and personalized learning environment for students of the Faculty of Education Sciences.